PENGEMBANGAN BAHAN AJAR BERBASIS E LEARNING PADA MATAKULIAH EVALUASI PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA - Ira Vahlia (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2017)
The ability to evaluate learning is a basic skill that must be mastered by students as prospective teachers. Based on this, it is necessary a teaching materials that help students and lecturers during the lecture. Students can know and understand about learning evaluation. In addition, the existence of teaching materials can help students to improve students' skills in understanding the material. In order for students to learn independently and adapt to technology, e-learning is needed based on teaching materials where lecturers do not have to guide students one by one, but the students can also help each other with the help of internet. The research was conducted at Muhammadiyah University of Metro and the subject of the research was 6th semester students consisting of 2 classes. Class A as an experimental class whereas class B as control class. The development of e-learning-based teaching materials uses the main 4-D development model of Define, Design, Develop, and Disseminate or adapted into 4-P model, defining, designing, developing, and deploying. The results of this study indicate that: 1) Teaching materials based on e-learning can support lecturing evaluation of learning in mathematics education program. This can be seen from the percentage of student response questionnaires of 80% that fulfill the criteria is quite valid; 2) Teaching materials based on e-learning can optimize student learning outcomes. This can be shown in student learning outcomes that achieve optimal learning outcomes of 87.5%